Analisis Kesalahan Siswa Kelas VIII Setelah Penerapan Model Pembelajaran Problem Based Learning pada Materi Teorema Phytagoras untuk Siswa SMP Kristen Waimangura - Kira, Emirensiana Irene Lali; Lede, Yulius Keremata; Making, Samuel Rex M.; Lubur, Dorothea Noviana Ludo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze students' errors in solving Pythagorean theorem problems using the Problem Based Learning (PBL) learning approach. The method used is a qualitative method with a descriptive approach aimed at determining the types of errors in solving Pythagorean Theorem problems after PBL. The results of the study showed that students' errors varied, ranging from conceptual errors such as understanding the definition of the Pythagorean theorem to procedural errors such as errors in calculations and use of formulas. These errors are influenced by students' understanding of basic concepts, problem-solving skills, and students' ability to apply the Pythagorean theorem in various problem contexts. The results of the study showed that students' abilities in solving Pythagorean Theorem problems that answered the questions correctly were still lacking. The cause of the errors made by students was that students were not careful in reading the questions, were not careful in understanding the questions so that they made mistakes in writing what was known and what was asked, so that they were less able to solve the questions so that they made mistakes in solving the questions.